PENGARUH LAYANAN KONSELING KELOMPOK DENGAN MENGGUNAKAN TEKNIK EXPRESSIVE WRITING BENTUK KATARSIS TERHADAP PENINGKATAN PENGENDALIAN EMOSI PADA SISWA KELAS VII B SMP NEGERI 9 BENGKULU TENGAH - Febrin Puspita Sari; Syahriman; Sri Saparahayuningsih (Consilia : Jurnal Ilmiah Bimbingan dan Konseling, 2023)
This study aims to describe the effect of group counseling services using the expressive writing technique in the form of catharsis on increasing emotional control of class VII B students of SMP Negeri 9 Bengkulu Tengah. Methods This research uses an experimental method with one group pretest posttest design. The population in this study were students of class VII B SMP Negeri 9 Bengkulu Tengah, totaling 30 students. The research sample was taken by purposive sampling technique with a sample of 6 students. Data collection techniques using a questionnaire. The research data were analyzed using statistical analysis with the t test formula. the results of the study are 1. students’ emotional control before being given group counseling service with expressive writing techniques in the form of catharsis are classified as low 2. students’ emotional control after being given group counseling services are classified as high 3. there is an influence of group counseling services with expressive writing techniques in the form of catharsis on increasing emotional control in class VII B of SMP Negeri 9 Bengkulu Tengah. Based on this research, the researchers provide advice to guidance and counseling teachers to provide group counseling services to increase emotional control.Keywords: Emotional Control, Group Counseling, Expressive Writing Technique in the form of Catharsis